18g=-17+17g

Simple and best practice solution for 18g=-17+17g equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 18g=-17+17g equation:



18g=-17+17g
We move all terms to the left:
18g-(-17+17g)=0
We add all the numbers together, and all the variables
18g-(17g-17)=0
We get rid of parentheses
18g-17g+17=0
We add all the numbers together, and all the variables
g+17=0
We move all terms containing g to the left, all other terms to the right
g=-17

See similar equations:

| 13=23-5b | | 11m-11m+4m+2m=12 | | k/4-3=3 | | 300+2x=295x | | 40=y/9+36 | | 15a-5a=-20 | | 9c+c-6c+3c-4c=9 | | 81=3+6b | | p/3-13=-11 | | 9c+c−6c+3c−4c=9 | | 7=63/r | | 16=2(h-7) | | s/2+30=39 | | 9x+41=180 | | 15m-13m=16 | | -2(y+4)=-7y=33 | | -15=1-(-4n) | | z/6-3=1 | | 5x+3x+10=6x-5 | | 11=5n+4 | | 97-z=32 | | 15y+3=184 | | 6=22-4f | | 1=c-1 | | 15p-3=5p-3 | | 20+p=-30 | | 10-2v=-5+50 | | 5p/7-6=-31 | | 7=4+3w | | 15p3=5p-3 | | -5(3-5n)=6n+4 | | 10x+33=6x-7 |

Equations solver categories